Effects of ultra‐strong static magnetic field on the gut microbiota of humans and mice - Zhao, Wen; Han, Yijuan; Shao, Dongyan; Han, Cuicui; Tian, Yixiao; Huang, Qingsheng (Bioelectromagnetics, 2023)
To explore the effect of ultra‐strong static magnetic field on gut microbiota, 16 T static magnetic field was used to study the changes in the structure and composition of human and mouse gut microbiota in this environment. In the mouse gut microbiota, at the genus level, the magnetic field significantly decreased the relative abundances of Escherichia‐Shigella, Lactobacillus, Enterococcus, Burkholderia‐Caballeronia‐Paraburkholderia, Parasutterella, and Ralstonia and significantly increased those of Parabacteroides, Alloprevotella, Alistipes, Odoribacter, Bacteroides, Mucispirillum, Sutterella, and Prevotellaceae_UCG‐001. Similarly, at the genus level, the relative abundances of Bacteroides, Parabacteroides, Romboutsia, and Streptococcus significantly decreased in the human gut microbiota. Contrary to the changing trend of the abundance in the mouse gut, the abundances of Bacteroides and Parabacteroides in the human gut were significantly reduced under magnetic field. The BugBase phenotypic prediction analysis showed that the relative abundances of five phenotypes, including anaerobism, mobile elements, potential pathogenicity, stress‐tolerant, and biofilm formation, changed significantly in the mouse gut microbiota, while the relative abundances of two phenotypes, including Gram‐positive and Gram‐negative phenotypes, changed significantly in the human gut microbiota. The 16 T magnetic field could differently affect the composition, structure, and phenotypes of gut microbiota in human and mice, suggesting the importance of model selection in studying the biological effects of magnetic field. Key points The ultra‐strong static magnetic fields are generally harmful to human health and are rarely encountered in daily life. With the recent advancements in science and technology, exposure to ultra‐strong static magnetic fields has increased in human daily life. So far, the effects of ultra‐strong static magnetic fields on gut microbiota, especially human gut microbiota, are lacking. The structure of gut microbiota is closely related to human health, so a 16 T ultra‐static magnetic field was used to study its effect on the structure of human and mouse gut microbiota. In mouse gut microbiota, 16 T ultra‐strong static magnetic field could significantly increase eight bacterial genera: Parabacteroides, Alloprevotella, Alistipes, Odoribacter, Bacteroides, Mucispirillum, Sutterella, and Prevotellaceae_UCG‐001. While 16 T ultra‐strong static magnetic field could significantly decrease the relative abundances of six bacterial genera: Escherichia‐Shigella, Lactobacillus, Enterococcus, Burkholderia‐Caballeronia‐Paraburkholderia, Parasutterella, and Ralstonia. In human gut microbiota, 16 T ultra‐strong static magnetic field could significantly decrease four bacterial genera: Bacteroides, Parabacteroides, Romboutsia, and Streptococcus: The relative abundances of Bacteroides and Parabacteroides have opposite trends in the guts of mice and humans. There are significant differences in the stress response of human and mouse gut microbiota to the ultra‐strong static magnetic field. The human gut microbiota presented higher tolerance to the ultra‐strong static magnetic field. This difference further suggested that the studies on the effects of ultra‐strong static magnetic field on gut microbiota should not be limited to mice.